Synthesis, characterization, quantum chemical calculations and anticancer activity of a Schiff base NNOO chelate ligand and Pd(II) complex - Ahmad, Nizam; Anouar, El Hassane; Tajuddin, Amalina Mohd; Ramasamy, Kalavathy; Yamin, Bohari M.; Bahron, Hadariah (PLOS ONE, 2020)
This paper reports the synthesis, characterization, anticancer screening and quantum chemical calculation of a tetradentate Schiff base 2,2'-((1E,1'E)-((2,2-dimethylpropane-1,3-diyl)bis- (azanylylidene))bis(methanylylidene))bis(4-fluorophenol) (L2F) and its Pd (II) complex (PdL2F). The compounds were characterized via UV-Visible, NMR, IR spectroscopy and single crystal x-ray diffraction. Density Functional Theory (DFT) and time-dependent DFT calculations in gas and solvent phases were carried out using B3LYP, B3P86, CAM-B3LYP and PBE0 hybrid functionals combined with LanL2DZ basis set. Complexation of L2F to form PdL2F was observed to cause a bathochromic shift of the maximum absorption bands of n–π* from 327 to 410 nm; an upfield shift for δ (HC = N) from 8.30 to 7.96 ppm and a decreased wavenumber for ν(C = N) from 1637 to 1616 cm-1. Overall, the UV-Vis, NMR and IR spectral data are relatively well reproduced through DFT and TD-DFT methods. L2F and PdL2F showed IC50 of 90.00 and 4.10 μg/mL, respectively, against human colorectal carcinoma (HCT116) cell lines, signifying increased anticancer activity upon complexation with Pd (II).